2018
DOI: 10.15361/2175-0106.2018v34n3p124-128
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Infectious and Parasitic Diseases in Association With the Outdoor Habits of Household Dogs and Cats a Case-Control Study

Abstract: Many owners believe to act in their pets' best interest by allowing them to go outside, with or without supervision. However, outdoor exposure greatly increases the risk of disease and accidents. In this study, we evaluated the association between infectious and parasitic diseases and the outdoor habits of pet dogs and cats. Epidemiological data were obtained from the records of dogs and cats treated at the Teaching Clinic and Hospital Unit of Veterinary Medicine in the city of Pirassununga, state of São Paulo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Also, in the present study, 75% of the cats with outdoor access were infected with parasites compared to only 22.22% among those who did not have outdoor access. Pereira et al (2018) reported that cats living outdoors had an increased risk of infection in comparison to indoor cats (OR 13.150;. A study by Zanzani et al (2014) had pointed out that the overall prevalence of intestinal parasites in household cats is statistically significantly higher than cats that lived outside or had access to a garden.…”
Section: Discussionmentioning
confidence: 99%
“…Also, in the present study, 75% of the cats with outdoor access were infected with parasites compared to only 22.22% among those who did not have outdoor access. Pereira et al (2018) reported that cats living outdoors had an increased risk of infection in comparison to indoor cats (OR 13.150;. A study by Zanzani et al (2014) had pointed out that the overall prevalence of intestinal parasites in household cats is statistically significantly higher than cats that lived outside or had access to a garden.…”
Section: Discussionmentioning
confidence: 99%